Kajian Analisis Desain Teknis Pemeliharaan Jalan Beton Desa Maluku Kec. Maritengngae Kab. Sidrap - St. Nurjannah Jamain; A. Sulfanita; Hamka Hamka; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Road maintenance or upkeep is not an easy problem to do because it requires quite a large amount of money. This is what causes the government to appear slow in repairing road damage so that the damaged roads become worse and wider. In reality, so far the government has carried out road maintenance and repairs when the road was in a condition that was in serious disrepair, so it is certain that the costs required will be very large and it can also be ascertained that the losses suffered by road users while the road is damaged, are also very large. big or even worthless. However, in implementing the preservation program, proper management is required so that the preservation program can be carried out effectively and efficiently. The aim of this research is to determine the type of damage found on concrete roads in Maluku Village, Kec. Maritengngae District. Sidrap along 2 km and technical study of concrete road maintenance program in Maluku Village, District. Maritengngae District. Sidrap along 2 km. The results of the research show that the damage on the concrete road in Maluku Village, Kec. Maritengngae District. Sidrap has patch damage, edge damage, cracks, transverse cracks, longitudinal cracks and holes. The most dominant damage is damage to holes and damage to roads on the concrete road in Maluku Village, Kec. Maritengngae District. Sidrap has 2 types of treatment, including Periodic Maintenance and Routine Maintenance Program. And handling the most dominant type of damage from STA 0+000 to 2+000 is a routine maintenance program of 100%.